2001
DOI: 10.1021/la010651o
|View full text |Cite
|
Sign up to set email alerts
|

Stable Dispersions of Fullerenes, C60 and C70, in Water. Preparation and Characterization

Abstract: Stable aqueous dispersions of fullerenes, C60 and C70, were prepared by simply injecting into water a saturated solution of fullerene in tetrahydofuran (THF), followed by THF removal by purging gaseous nitrogen. To our knowledge, this is the first report of the stable dispersion of C70 in water. Fullerenes are dispersed as monodisperse clusters in water, 60 nm in diameter. High resolution transmission electron microscopy revealed the polycrystalline nature of the cluster. The preparation of the dispersion is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
508
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(564 citation statements)
references
References 33 publications
51
508
0
5
Order By: Relevance
“…It strongly suggests that the primary mechanism of C 60 fullerene solubilization in water is the attachment of the OH groups to C 60 fullerene carbons, which explains why the lone C 60 molecules and their clusters exist at equilibrium in solution for quite a long time (see above), a feature that is independent of the method of C 60 FAS preparation. It also explains the irreversible character of the adsorption/desorption isotherms reported earlier, 27 the minimal extraction of C 60 fullerene from water−colloid solutions by toluene, 28 and the ability of C 60 fullerenes from C 60 FAS to hold water molecules even in vacuum. 17 The covalent attachment of the OH groups does not exclude the possibility of electron transfer from water molecules to C 60 fullerene, enabling us to explain the negative charge on fullerene particles.…”
Section: ■ Results and Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It strongly suggests that the primary mechanism of C 60 fullerene solubilization in water is the attachment of the OH groups to C 60 fullerene carbons, which explains why the lone C 60 molecules and their clusters exist at equilibrium in solution for quite a long time (see above), a feature that is independent of the method of C 60 FAS preparation. It also explains the irreversible character of the adsorption/desorption isotherms reported earlier, 27 the minimal extraction of C 60 fullerene from water−colloid solutions by toluene, 28 and the ability of C 60 fullerenes from C 60 FAS to hold water molecules even in vacuum. 17 The covalent attachment of the OH groups does not exclude the possibility of electron transfer from water molecules to C 60 fullerene, enabling us to explain the negative charge on fullerene particles.…”
Section: ■ Results and Discussionsupporting
confidence: 63%
“…17 The covalent attachment of the OH groups does not exclude the possibility of electron transfer from water molecules to C 60 fullerene, enabling us to explain the negative charge on fullerene particles. 17,18,28 However, the previous model of stabilization of hydrated C 60 fullerene by water molecules joined together by an H-bonding network 17,23 needs to be corrected in view of the available results of molecular dynamics simulations of hydrated C 60 fullerenes 29,30 reporting the weakening and breakage of the H bonds between water molecules in the immediate vicinity of the C 60 fullerene surface as a result of the overbalancing effect of C 60 fullerene−water with respect to the water−water interaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous work by Deguchi et al have shown it possible to create monodisperse clusters of C 60 (60 nm) in water through forced precipitation by addition of a THF-solution into water. [ 12 ] The thought was that a PCBM-analogue, that was not soluble in water, which would allow for subsequent processing, but still containing coordination properties towards aqueous media, might behave in a similar way if mixed with an aqueous solution from THF. The fullerene 2 (see Scheme 1 ) containing an advantages of solubility switching, removal of the side chains from the bulk of the active layer furthermore means removal of non-absorbing material, and several studies show enhanced stability of the active layer towards general degradation.…”
Section: Doi: 101002/aenm201000007mentioning
confidence: 99%
“…The most relevant feature of fullerene C 60 is the ability to act as a free radical scavenger [16]. Properties attributed to the delocalized double bond system of fullerene cage allow C 60 to quench various free radicals more efficiently than conventional antioxidants [10].…”
Section: Introductionmentioning
confidence: 99%